IJCM_1A: Connecting Compassionately: An Evaluation of Medical Graduates and Postgraduates Attitudes Toward Learning Communication Skills - Agrawal Jhilmil; Abedi Ali Jafar; Mehnaz Saira; Zubair Mohd. Yasir; Maheshwari Veena (Wolters Kluwer Medknow Publications, 2024)
Background: Good communication skills are crucial for clinicians, influencing patient health and satisfaction. These skills build trust between patients and providers, preventing risks and conflicts. The 2019 introduction of the Attitude, Ethics, and Communication (AETCOM) module in MBBS curriculum by the Medical Council of India aims to enhance medical students' communication skills, curb malpractices, and uphold patient's trust in doctors. Methodology: It's a cross-sectional study conducted in the Department of Community Medicine, J. N. Medical College, AMU, Aligarh. A total of 478 medical-graduates and PGs (divided into four groups of first (2023), second (2022+2021), third (2020+2019) MBBS-batch and fourth (Interns+ PGs) groups) were enrolled to fill up the communication skills attitude scale (CSAS) questionnaire online which consists of 13 positive and 13 negative, and also 13 affective, 5 cognitive and 4 respect attitude questions which was scored in five-point Likert's scale. The data was analyzed using SPSS 20.0 software. Results: Overall score for positive, negative, affective, cognitive and respect domain were 36.6±7.0, 54.3±6.2, 43.5±4.6, 17.4±2.1 and 17.0±2.3 respectively. There is significant difference in score of negative attitude of first group with second and third group (34.4 vs 37.5, p=0.003 and 34.4 vs 37.8, p=0.001) respectively while positive attitude remained same. Also, significant difference in affective (42.6 vs 44.3, p=0.036) and cognitive (17.1 vs 17.9, p=0.034) component between first and fourth group while no such difference was found in respect attitude. Conclusion: Study reveals a positive inclination among medical graduates and PGs towards CSLP while a decrease in negative attitude of interns and PGs from final year students, may be due to increase in clinical exposure with the patients. The favorable attitude underscores the potential for successful integration of such programs into medical education, fostering effective communication, enhancing the quality of patient care.